Educación de calidad y en competencias para la competitividad o para la cooperación - López Herrerías, José Ángel (Revista Complutense de Educación, 2010)
The purpose of this paper is to analyse and value the perspective of education in “quality” and in “competences”, inserted into an economical globalization. The education must focus on the promotion of those persons capable of making an effort not to achieve competitive results, which are bound to have conflictive consequences, but to succeed in participation and cooperation, so that all of us can be participant of their success. Surpassing learning competences to be competitive as a negative product. They generate less sustainable development, less justice and solidarity, less Human Wrights.